Inovasi digitalisasi promosi potensi dan produk usaha masyarakat desa berbasis website di Desa Bangsal Kecamatan Pampangan - Anita Desiani; Sugandi Yahdin; Irmeilyana Irmeilyana; Desty Rodiah (Riau Journal of Empowerment, 2020)
Bangsal Village is in the South Sumatra region within the district of Ogan Komering Ilir, Pampangan District. Bangsal Village ha potential including buffalo milk, sugar puan, sagon, penjem (a kind of yogurt), curd (a kind of butter for cooking oil), smoked-fish, fish-crackers and swamp-rice with high iron mineral (Fe). Almost the majority of Bangsal villagers are buffalo breeders. The potential possessed by Bangsal Village, if developed, is expected to make the villages has food sovereignty, economic independence and local wisdom as personality in culture. One of the media that can help develop it is Computer and Information Technology (ICT). The ICT can be used as the development of village websites. Bangsal village website can be a media for promotion of potentials and products owned by Bangsal Village. With the website everyone can easily search for information and get to know the Bangsal village without having to go directly to the village. The development of the Bangsal village website requires an active role from the Bangsal village community and community itself. Website management training that has given to several village community participants showed good results. These can be seen from the ability of participants to complete more than 70% of the tasks given by the trainer.